Quality assurance practices, an identifier of entrepreneurial universities in France - Romain Pierronnet (Projectics)
Universities are complex organizations, if only because they involve many stakeholders, along with collegial bodies in which issues of power are at stake. Thus, understanding the mechanisms of decision-making within university organizations has been a recurring issue for several decades. In France, the IRU law (2007) aimed to develop the management autonomy of universities, and they had to reorganize themselves accordingly, reshuffling the distribution of powers and processes within the organizations to make them more entrepreneurial. To account for this, we discuss in an exploratory way the deployment of quality assurance practices within a university, which will lead us to recommend that this is utilized as an important index for the transformations that French universities are undergoing.